Three-pathway combination for glutathione biosynthesis in Saccharomyces cerevisiae - Tang, Liang (Microb Cell Fact, 2015)
BACKGROUND: Glutathione (GSH), a pivotal non-protein thiol, can be biosynthesized through three pathways in different organisms: (1) two consecutive enzymatic reactions catalyzed by γ-glutamylcysteine synthetase (Gsh1 or GshA) and glutathione synthetase (Gsh2 or GshB); (2) a bifunctional γ-glutamylcysteine synthetase/glutathione synthetase (GshF); (3) an alternative condensation of γ-glutamyl phosphate synthesized by γ-glutamyl kinase (Pro1 or ProB) with cysteine to form γ-glutamylcysteine which was further conjugated to glycine by glutathione synthetase. The Gsh1 and Gsh2 of conventional GSH biosynthetic pathway or the bifunctional GshF reported previously have been independently modulated for GSH production. This study developed a novel three-pathway combination method to improve GSH production in Saccharomyces cerevisiae. RESULTS: A bifunctional enzyme GshF of Actinobacillus pleuropneumoniae was functionally expressed in S. cerevisiae and Pro1 in proline biosynthetic pathway was exploited for improving GSH yield. Moreover, two fusion proteins Gsh2-Gsh1 and Pro1-GshB were constructed to increase the two-step coupling efficiency of GSH synthesis by mimicking the native domain fusion of GshF. The engineered strain W303-1b/FGP with three biosynthetic pathways presented the highest GSH concentration (216.50 mg/L) and GSH production of W303-1b/FGP was further improved by 61.37 % when amino acid precursors (5 mM glutamic acid, 5 mM cysteine and 5 mM glycine) were fed in shake flask cultures. In batch culture process, the recombinant strain W303-1b/FGP also kept high efficiency in GSH production and reached an intracellular GSH content of 2.27 % after 24-h fermentation. CONCLUSIONS: The engineered strains harbouring three GSH pathways displayed higher GSH producing capacity than those with individually modulated pathways. Three-pathway combinatorial biosynthesis of GSH promises more effective industrial production of GSH using S. cerevisiae. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-015-0327-0) contains supplementary material, which is available to authorized users.